KOMUNIKASI ANTARA PEMELUK AGAMA MINORITAS ISLAM DAN PENGANUT AGAMA MAYORITAS HINDU DI KABUPATEN KERANGASEM BALI - Hery Bambang Cahyono (Universitas Muhammadiyah Jember, 2020)
Living together peacefully in a different society is not easy. Adherents of minority Muslims and majority Hindus in Karangasem Bali is a clear proof. They are able to work together to advance the region without meaningful conflict. Even though in Lampung Province there is still frequent friction between two religious adherents. An interesting problem is; how is the communication between these two elements of society and how to solve if there are problems that arise. The theory used is interpresonal communication by taking a role theory model. The method used is descriptive qualitative while the location stabilizes is At-Taqwiin Islamic Boarding School in Karangasem Regency, Bali. The result is that the community is accustomed to working in social, economic, political to social matters, while many religious issues are left to the kiai and religious teachers in the pesantren. The kiai has laid the foundation of harmonious communication and if there is a problem, the kiai always helps solve it.